The rule of law approach for more resilient institutions: Judicial accountability and independence, and global economic activities - Sultan Mehmood (Asian Development Bank Institute (ADBI), 2023)
This policy paper explores the judiciary's pivotal role in development, covering property rights, government accountability, and contract enforcement. It underscores the importance of impartial judicial institutions, focusing on independence, accountability, and their role in stabilizing global supply chains and financial systems. In the first part, we derive three key policy implications from two research papers. First, we stress the significance of independent judicial appointments to enhance decision-making and economic integrity. Appointments based on merit, rather than political favoritism, bolster public trust and guard against judicial compromise. Second, we advocate for understanding the interplay between cultural norms and political institutions. We propose measures to separate religious and political power, including affirmative action in religious education regions and secularization of bureaucracies. Lastly, we call for the creation of judicial selection procedures to insulate judges from political influence, promoting an independent and accountable judiciary.
Keywords: D72; K40; O17; K10; Z12; 330; presidential appointment; religious elites; governance; courts